The effect of workplace mobility on air pollution exposure inequality-a case study in the Central Belt of Scotland - Tomáš Liška; Mathew R Heal; Chun Lin; Massimo Vieno; Edward J Carnell; Samuel J Tomlinson; Miranda Loh; Stefan Reis (IOP Publishing, 2024)
A large number of epidemiological studies have identified air pollution as a major risk to human health. Exposures to the pollutants PM _2.5 , NO _2 and O _3 cause cardiovascular and respiratory diseases, cancer and premature mortality. Whilst previous studies have reported demographic inequalities in exposure, with the most deprived and susceptible often being disproportionately exposed to the highest pollutant concentrations, the vast majority of these studies have quantified exposure based only on individuals' place of residence. Here we use anonymised personal data from UK Census 2011, and hourly modelled air pollution concentrations at 0.8 km × 1.4 km spatial resolution in the Central Belt of Scotland, to investigate how inclusion of time spent at place of work or study affects demographic inequalities in exposure. We split the population by sex, ethnic group, age and socio-economic status. Exposure gradients are observed across all demographic characteristics. Air pollution exposures of males are more affected by workplace exposures than females. The White ethnic group has the lowest exposures to NO _2 and PM _2.5 , and highest to O _3 . Exposures to NO _2 and PM _2.5 tend to peak between the ages of 21 and 30, but those aged 31-50 tend to be most impacted by the inclusion of time spent at workplace in the exposure assessment. People in the two least deprived deciles consistently have the lowest residential-only and combined residential-workplace exposure to NO _2 and PM _2.5 , but experience the highest increase in exposure when including workplace. Overall, including workplace exposure results in relatively small change in median exposure but attenuates some of the exposure inequalities associated with ethnicity and socioeconomic status observed in exposure assessments based only on place of residence.